Trichoderma fungi for the protection of greenhouse crops against oomycete Pythium sp. - Scerbacova, T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To identify a highly virulent fungus Trichoderma Pers. ex Fr. to protect greenhouse crops from the pathogen Pythium sp.Methods. The objects of research were strains/isolates of Trichoderma sp. from the working collection of the laboratory. The pathogen Pythium sp. was isolated from mineral wool used in a hydroponic greenhouse. The pathogenicity of Pythium sp. was determined by infecting cucumber seedlings in a humid chamber at 24°C. To select active strains of Trichoderma against Pythium sp., their antagonistic activity was studied by the method of double cultures. On day 10, the inhibition rate of fungi by each other (%) was determined.Results. When determining the pathogenicity of the isolate Pythium sp. against cucumber seedlings on day 4, 100% death of all sprouts occurred. When studying the antagonism of Trichoderma and Pythium sp. fungi, a high growth rate of oomycete was observed in the control. In 50 h after sowing, the pathogen colonized the entire agar plate. However, in double cultures, Trichoderma fungi inhibited the growth of oomycete. On day 10, 4 strains: T. lignorum (syn. T. viride) CNMN-FD-14, T. asperellum, T. koningii and Trichoderma sp. 1K colonized the pathogen with an inhibition rate of 100%. Other Trichoderma fungi inhibited the pathogen by 83.5—94.1%.Conclusions. Trichoderma strains with high inhibitory activity can be used as a producer of a biological product for the protection of greenhouse crops from Pythium sp. oomycete.